WASH phosphorylation balances endosomal versus cortical actin network integrities during epithelial morphogenesis - Vasilios Tsarouhas (Nature Portfolio, 2019)
The regulation and coordination of F-actin networks are not well understood. Here, the authors show an antagonistic relationship between endosomal F-actin assembly and cortical bundle integrity during epithelial tube maturation that is regulated by kinase and phosphatase activity modifying WASH.